Generic status of Winitia (Annonaceae, Miliuseae) reaffirmed by molecular phylogenetic analysis, including a new species and a new combination from Thailand - Chaowasku, Tanawat; Aongyong, Kithisak; Damthongdee, Anissara; Jongsook, Hathaichanok; Johnson, David M. (European Journal of Taxonomy, 2020)
The generic status of Winitia Chaowasku (Annonaceae Juss., Miliuseae Hook.f. & Thomson) is reaffirmed by an extensive phylogenetic reconstruction using seven plastome regions (matK, ndhF, rbcL, ycf1 exons; trnL intron; psbA-trnH, trnL-trnF intergenic spacers) and including, among others, seven accessions of Winitia plus two accessions of its sister group, Stelechocarpus Hook.f. & Thomson. The results disclosed a maximally supported clade of Winitia, as well as of Stelechocarpus. The sister relationship of the two genera is still rather poorly supported and the branch uniting them is very short, whereas the branches leading to Winitia and to Stelechocarpus are relatively long, corresponding to their considerable morphological differences. Additionally, in Miliuseae there is a particular indel of eight continuous base pairs in the trnL-trnF intergenic spacer potentially diagnostic for generic discrimination, i.e., members in the same genus possess the same indel structure (absence or presence of a gap), and this indel differentiates Winitia from Stelechocarpus. Winitia cauliflora (Scheff.) Chaowasku appears polyphyletic and Winitia longipes (Craib) Chaowasku & Aongyong comb. nov. based on Stelechocarpus longipes Craib is consequently proposed. Furthermore, our phylogenetic data support a new species, Winitia thailandana Chaowasku & Aongyong sp. nov. from southern Thailand, which is described and illustrated. A key to genera in the sageraeoid clade (Sageraea-Winitia-Stelechocarpus) and a key to the four species of Winitia are provided.